Trends for in-office usage of pharmacological sedation agents in India: A narrative review - Sakshi Joshi; Anil Gupta; Shalini Garg; Shikha Dogra (Journal of Anaesthesiology Clinical Pharmacology, 2022)
Background and Aims: Conscious sedation plays a significant role in in-office pharmacological behavior management for short-term procedures in children and apprehensive adults. The advantage conscious sedation provides is by improving quality of care provided by decreasing pain and anxiety while maintaining a patent airway and adequate spontaneous ventilation. Methodology: Present review was conducted to evaluate recent trends regarding use of in-office pharmacological sedation agents in India. A rigorous search was conducted through five electronic databases namely PubMed, Scopus, Web of Science, Cochrane Database, and CTRI (Clinical Trial Registry – India). The search period was defined to be last 5 years, that is, from 1st January 2014 to 31st July 2019. Terminologies “Conscious Sedation,” “In-office Sedation,” “Midazolam,” “Nitrous Oxide,” “India” were included in the search. The Boolean Operation “OR” and “AND” were applied to combine the terminologies. Results: A total of 20 studies were identified following strict inclusion and exclusion criteria. The included studies were evaluated for study design, speciality involved, number of individuals and their age groups, drugs compared along with route and dosage, procedures undertaken, place of study and results. Dental fraternity (13) had more number of trials conducted as compared to medical fraternity (7) in the stimulated period, with South Indian region having maximum trials registered or published. Conclusion: Midazolam was observed to the drug of choice for in-office sedation procedures in Indian Scenario. The limitation of study is that the published clinical studies are limited to a few states of India.